Возможности искусственных голосовых аппаратов - Мукановская, И. В.; Дацок, О. М. (ХНУРЭ, 2017)
The given work is devoted to the modern developments in the field of artificial voice apparat. At the work considered the basic definitions, characteristics and prospects of development of artificial voice apparat.
Keywords: биомединженерия; гортань